2021
DOI: 10.1002/adhm.202002104
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor‐Based Strategies for Synergistic Cancer Therapy

Abstract: Immune checkpoint blockade therapy (ICBT) targeting checkpoints, such as, cytotoxic T‐lymphocyte associated protein‐4 (CTLA‐4), programmed death‐1 (PD‐1), or programmed death‐ligand 1 (PD‐L1), can yield durable immune response in various types of cancers and has gained constantly increasing research interests in recent years. However, the efficacy of ICBT alone is limited by low response rate and immune‐related side effects. Emerging preclinical and clinical studies reveal that chemotherapy, radiotherapy, phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 199 publications
(174 reference statements)
0
39
0
Order By: Relevance
“…Since the efficacy of PD-1 inhibitor monotherapy in STSs is extremely low, the use of various methods to reprogram the tumor microenvironment from immune-"cold" to immune-"hot" to increase the sensitivity of PD-1 inhibitors in STS is a promising approach [18,20]. Potential mechanisms of the combination therapy of PD-1 inhibitors with cytotoxic chemotherapy agents include immunogenic tumor cell death, anti-angiogenesis, selective depletion of myeloid immunosuppressive cells, reduction of tumor-induced immune suppression, and the sensitization of tumor cells to the immune response [20,29]. One patient with angiosarcoma had a complete response (100% decrease in target lesion size), six patients had a partial response (30% and more decrease in target lesion size), seven patients had stable disease (< 20% increase and < 30% decrease in target lesion size), and 14 patients had progressive disease (20% and more increase in target lesion size).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the efficacy of PD-1 inhibitor monotherapy in STSs is extremely low, the use of various methods to reprogram the tumor microenvironment from immune-"cold" to immune-"hot" to increase the sensitivity of PD-1 inhibitors in STS is a promising approach [18,20]. Potential mechanisms of the combination therapy of PD-1 inhibitors with cytotoxic chemotherapy agents include immunogenic tumor cell death, anti-angiogenesis, selective depletion of myeloid immunosuppressive cells, reduction of tumor-induced immune suppression, and the sensitization of tumor cells to the immune response [20,29]. One patient with angiosarcoma had a complete response (100% decrease in target lesion size), six patients had a partial response (30% and more decrease in target lesion size), seven patients had stable disease (< 20% increase and < 30% decrease in target lesion size), and 14 patients had progressive disease (20% and more increase in target lesion size).…”
Section: Discussionmentioning
confidence: 99%
“…Each line represents the change in the size of a patient's target lesion over the time of treatment. Patients with a complete or partial response are indicated in green, those with progressive disease in red, and those with stable disease in yellow Chemotherapy combined with a PD-1 inhibitor has been shown to have a beneficial effect against various other malignancies [20,25,29]. Recent clinical trials have demonstrated the efficacy and safety of the combination of the PD-1 inhibitor, pembrolizumab, and the chemotherapy drug, doxorubicin, for treating patients with advanced STS [22,30].…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon was also reported in other polymer systems. [ 21,26 ] Interestingly, the functionalization of p(lys‐ r ‐leu) with guanidinium functional groups also led to an increase in its hemolytic activity. Considering the high hemolytic activity of random copolymers p(lys‐ r ‐leu) and p(lys(Gua)‐ r ‐leu), subsequent studies were focused on the hydrophilic and amphiphilic homopolymers instead.…”
Section: Resultsmentioning
confidence: 99%
“…This was also observed with guanidinium‐functional polycarbonates. [ 26 ] There might be other mechanisms of action involved, which would be further explored in the future. On the other hand, red fluorescence was observed in part of the bacterial cells after incubation with PLL 22 ‐Gua‐VitE for 1 h, indicating that the polymer caused membrane disruption to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…The development of checkpoint inhibitors, monoclonal antibodies that bind to and block the interactions of PD-1 and CTLA-4 with their cognate ligands, inhibits this interaction stimulating tumour clearing in a subset of patients [52]. However, a significant number of cancer patients do not respond to checkpoint inhibitors, presumably because they have tumours with immunologically cold TMEs where CTLs are not activated or trafficked [53,54]. Activation of STING by CDNs has significant potential to enhance current cancer immunotherapy treatments by inducing inflammation in these immunologically cold tumours to synergize with checkpoint inhibitors.…”
Section: Stinging Cancer: a New Class Of Immunotherapymentioning
confidence: 99%